2020
DOI: 10.1002/pssa.201900796
|View full text |Cite
|
Sign up to set email alerts
|

Improving AlN Crystal Quality and Strain Management on Nanopatterned Sapphire Substrates by High‐Temperature Annealing for UVC Light‐Emitting Diodes

Abstract: Herein, AlN growth by metalorganic vapor‐phase epitaxy on hole‐type nanopatterned sapphire substrates is investigated. Cracking occurs for an unexpectedly thin‐layer thickness, which is associated to altered nucleation conditions caused by the sapphire pattern. To overcome the obstacle of cracking and at the same time to decrease the threading dislocation density by an order of magnitude, high‐temperature annealing (HTA) of a 300 nm‐thick AlN starting layer is successfully introduced. By this method, 800 nm‐th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 31 publications
0
19
0
Order By: Relevance
“…The applied TDD calculation procedure provides reliable results, since the estimated TDDs correlate well with TDDs determined by defect etching with a KOH solution (analyzed area of 10 µm x 10 µm) and dark spot densities determined by cathodoluminescence (CL) spectroscopy. [ 20,21 ]…”
Section: Methodsmentioning
confidence: 99%
“…The applied TDD calculation procedure provides reliable results, since the estimated TDDs correlate well with TDDs determined by defect etching with a KOH solution (analyzed area of 10 µm x 10 µm) and dark spot densities determined by cathodoluminescence (CL) spectroscopy. [ 20,21 ]…”
Section: Methodsmentioning
confidence: 99%
“…On the other hand, the hexagonal phase of AlGaN presents the advantage over the cubic phase of requiring a lower concentration of Al to reach higher E g ; nonetheless, when working with h-AlGaN, it is very important to consider that built-in internal electric fields cause a large shift to lessenergetic emission [80], as will be discussed in the next sections. In general, due to the fact that the hexagonal structure is the stable phase of III-nitrides, the state of art unfolds studies that support sapphire as the main substrate in UVC LED growth [74,[81][82][83][84][85][86][87].…”
Section: Substrate and Buffer Layermentioning
confidence: 99%
“…A dual coalescence of the AlN epilayer was observed, which can effectively relax strain during the heteroepitaxy process. In 2020, Hagedorn et al reported an 800 nm-thick, fully coalesced, and crack-free AlN grown on two-inch hole-type nanopatterned sapphire wafers by high-temperature annealing (1680 °C) method 86 .
Fig.
…”
Section: Manipulation Of Strain Fieldsmentioning
confidence: 99%